Regulation of PDGFC signalling and extracellular matrix composition by FREM1 in mice - Fenny Wiradjaja; Denny L. Cottle; Lynelle Jones; Ian Smyth (The Company of Biologists, 2013)
SUMMARY Fras1-related extracellular matrix protein 1 (FREM1) is required for epidermal adhesion during embryogenesis, and mice lacking the gene develop fetal skin blisters and a range of other developmental defects. Mutations in members of the FRAS/FREM gene family cause diseases of the Fraser syndrome spectrum. Embryonic epidermal blistering is also observed in mice lacking PdgfC and its receptor, PDGFRα. In this article, we show that FREM1 binds to PDGFC and that this interaction regulates signalling downstream of PDGFRα. Fibroblasts from Frem1-mutant mice respond to PDGFC stimulation, but with a shorter duration and amplitude than do wild-type cells. Significantly, PDGFC-stimulated expression of the metalloproteinase inhibitor Timp1 is reduced in cells with Frem1 mutations, leading to reduced basement membrane collagen I deposition. These results show that the physical interaction of FREM1 with PDGFC can regulate remodelling of the extracellular matrix downstream of PDGFRα. We propose that loss of FREM1 function promotes epidermal blistering in Fraser syndrome as a consequence of reduced PDGFC activity, in addition to its stabilising role in the basement membrane.